Matka naszego Pana czy Królowa Męczenników - Wojciech Życiński (Polonia Sacra)
The Queenship of Mary must be inserted within the kingly status of the People of God. The insertion of Our Lady’s Queenship into the context of the kingly office of the People of God, while not detaching the person of Mary from the ecclesial community, help us to understand the meaning of Marian Queenship and its challenges for contemporary Christians. In her quality as excelling member of the Church, Mary the Queen proclaims the royal character of the other human beings, which is founded on union with Christ. She understood her life as a service, in which consists royalty according to the Gospel (Lk 22, 24–40). She did not construe her Divine Motherhood as expression of sovereignty but declared herself servant of the Lord worshiping the one God and completely given to service for His plan o salvation. Whereas worldly kingship is expressed by domination, imposition, and egoistic pursuits, the kingship of Christ is manifested in the rejection of violence and in love and service of the truth, unto the total giving of self. In this perspective Mary is one who has inherited the Kingdom of God, because she shares in the power communicated by the Spirit for delivering the world from its evils and for bringing people to Divine filiation and Christian maturity.